Hubungan kausalitas ekspor batubara dengan pertumbuhan ekonomi Provinsi Jambi - Iis Puji Wahyuni; Amri Amir; Rahma Nurjanah (e-Journal Perdagangan Industri dan Moneter, 2020)
In this study aims to (1) know the development of economic growth and know the development of coal exports (2) find out the causality of coal exports with the economic growth of Jambi Province. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS) of Jambi Province. To answer these objectives, this study uses a type of quantitative descriptive research with an analysis model for the first and second problems using simple regression analysis and granger causality test. The results of the study show that (1) the average development of economic growth in Jambi Province in 2004-2018 was 6.15 percent; (2) the average development of coal exports is 149.64 percent, and (3) partially coal exports do not have a causal relationship to the economic growth of Jambi Province  Keywords: Economic growth, Coal exports